Uwarunkowania konkurencyjności produkcji jaj spożywczych na przykładzie wybranej fermy - Krawczyk, Józefa; Sokołowicz, Zofia (Factors of Table Egg Production Competitiveness Using the Example of a Selected Farm, 2006)
The aim of the study is to evaluate the possibility of improving the competitiveness of table egg production by determining the optimum date of chicken culling in a randomly chosen layer farm using the marginal calculus method.Source data were collected in 2003-2004. The study covered two commercial flocks of Hy-Line Brown laying hens that were used in the same period. Flock A (6200 layers) was composed of hens subjected to moulting at 64 weeks of age, and flock В (6000 layers) was reared and used on the farm in the first year of egg production.In a market economy, the competitive edge is gained by producers able to determine the optimum date on which inefficient production should be discontinued and its profile changed. In the case of egg production, this means that young layers should be introduced to the poultry house. Production on the experimental farm was profitable thanks to the producer's active marketing and regular monitoring of prices, because during the analysed period it was difficult to sell table eggs on the Polish market and many smaller companies were edged out of the market. The use of the marginal calculus was found to be useful for determining the profitability threshold and the optimum date of hen flock liquidation in an unstable market characterized by changing prices.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 491-496